The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/mnfr.201600843
|View full text |Cite
|
Sign up to set email alerts
|

An isoflavone enriched diet increases skeletal muscle adaptation in response to physical activity in ovariectomized rats

Abstract: Our results indicate that the combination of ISOs and exercise is more efficient in increasing relative skeletal muscle mass and the expression of molecular markers related to anabolic adaptation in the skeletal muscle of female rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In rat L6 skeletal muscle cells, genistein promoted cells proliferation at doses ≤ 1 µM, which is in agreement with our datademonstrating a stimulation of protein synthesis in C2C12 myotubes at the same dose [16]. Our data are also in line with our previous in vivo studies demonstrating that isoflavones increased soleus muscle weight in ovariectomized female rats [17,18]. Interestingly, our investigations also demonstrate that treatment with E2, SoyEx, isoflavones, and Mix resulted in a higher number of myotubes per area compared to the control cells (▶ Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In rat L6 skeletal muscle cells, genistein promoted cells proliferation at doses ≤ 1 µM, which is in agreement with our datademonstrating a stimulation of protein synthesis in C2C12 myotubes at the same dose [16]. Our data are also in line with our previous in vivo studies demonstrating that isoflavones increased soleus muscle weight in ovariectomized female rats [17,18]. Interestingly, our investigations also demonstrate that treatment with E2, SoyEx, isoflavones, and Mix resulted in a higher number of myotubes per area compared to the control cells (▶ Fig.…”
Section: Discussionsupporting
confidence: 93%
“…ER-β is expressed and localized within skeletal muscle tissue [ 21 ], and ER-β activation appears to regulate signaling pathways important for skeletal muscle growth and regeneration [ 22 ]. In animals, a number of studies have investigated the influence of isoflavones found in soy (mainly genistein and daidzein) on skeletal muscle [ 23 , 24 , 25 , 26 ]. The results are promising, showing reduced muscle atrophy [ 23 , 24 ], lower expression of ubiquitin-specific protease 19 through ER-β activation [ 25 ], and an improved anabolic response to training in rats, accompanied by higher expression of myogenic regulatory factors [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a significant increase in the IGF‐1 mRNA levels might require increased β 2 ‐AR expression along with a supply of its ligand. Since the ER agonist activity of isoflavones is widely acknowledged to contribute to increasing muscle mass and preventing atrophy, multiple activities of GEN in addition to increasing β 2 ‐AR gene expression may be involved in improving skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%